Hereditary melanoma: a five-year study of Brazilian patients in a cancer referral center - phenotypic characteristics of probands and pathological features of primary tumors - Bianca Costa Soares de Sá; Luciana Facure Moredo; Elimar Elias Gomes; Erica Sara Souza de Araújo; João Pedreira Duprat (Sociedade Brasileira de Dermatologia, 2018)
Abstract: BACKGROUND: Approximately five to 10% of all melanomas occur in families with hereditary predisposition and the main high-risk melanoma susceptibility gene is the CDKN2A. OBJECTIVES: To describe, after a five-years study, the clinical data of patients (probands) from familial melanoma kindreds, and the pathological characteristics of their melanoma. METHODS: The inclusion criteria were melanoma patients with a family history of melanoma or pancreatic cancer (first- or second-degree relatives) or patients with multiple primary melanomas (MPM). RESULTS: A total of 124 probands were studied, where 64 were considered familial cases and 60 MPM. Mean age at diagnosis was 50 years. Our results show that the following characteristics were prevalent: skin phototype I/II (89.5%), sunburn during childhood (85.5%), total number of nevi ≥50 (56.5%), Breslow thickness ≤1.0mm (70.2%), tumors located on the trunk (53.2%) and superficial spreading melanomas (70.2%). STUDY LIMITATIONS: Analyses of probands' relatives will be demonstrated in future publication. CONCLUSIONS: Our findings are in agreement with previous familial melanomas reports. Fifteen new melanomas in 11 patients were diagnosed during follow up, all of which were ≤1.0 mm. This is the largest dataset of Brazilian melanoma prone kindreds to date, thus providing a complete database for future genetic studies.